Retratos de resistencia campesina ante el extractivismo minero: un análisis del documental “Hija de la Laguna (2015)” - Luna Paredes, Andrea (Pontificia Universidad Católica del Perú, 2024)
The article analyzes the film “Hija de la laguna” (2015) as a paradigmatic case of socio-environmental documentary, whose purpose is to mark a political position through the image and audiovisual treatment in order to position itself in favor of the environmental struggles, in this case, against mining extractivism, as it seeks to portray peasant demands, taking into account the point of view of activist Nélidad Ayay.

El artículo analiza la pieza cinematográfica “Hija de la laguna” (2015) como un caso paradigmático de documental socio-ambiental, cuyo propósito es marcar una postura política a través de la imagen y el tratamiento audiovisual con el fin de posicionarse a favor de las luchas ambientales, en este caso, frente a la extractividad minera, en tanto busca retratar las demandas campesinas, tomando en cuenta el punto de vista de la activista Nélida Ayay.
Portraits of Peasant Resistance to Mining Extractivism: An Analysis of the Documentary “Daughter of the Lake (2015)”
Keywords: Peruvian documentary; Mining; Extractivism; Peasant organisation; Documental peruano; Extractivismo minero; Organización campesina; https://purl.org/pe-repo/ocde/ford#5.04.03